Hydromagnetic natural convection in a wavy-walled enclosure equipped with hybrid nanofluid and heat generating cylinder - Mohammad Mokaddes Ali; Rowsanara Akhter; M.A. Alim (Alexandria Engineering Journal, 2021)
Flow and heat transfer components of buoyancy driven convection in a hybrid nanofluid filled wavy-walled cavity are numerically investigated in this study. A cylindrical heat generating blockage is placed at the center of the cavity. The cavity is partially heated from its bottom wall and cooled from wavy-walls while the remaining walls are adiabatic. The cavity is permeated by a transverse magnetic field. Thermal conductivity model of hybrid nanofluid is developed comprising Brownian motions of different nanoparticles. The non dimensional governing equations are solved by implementing finite element method. Obtained results demonstrate the intensification of fluid flow circulation for increasing Rayleigh number and heater length. The heat transfer rate is expeditiously augmented for increase in Rayleigh number and hybrid nanoparticles volume fraction but reverse trend is observed for higher Hartmann number. The flow circulation and temperature distribution are influenced with the presence of heat generating cylinder and roughness of the cavity walls. In addition, strength of fluid motion becomes higher for wavy cavity containing heat generating obstacle compared to smooth cavity without blockage. Maximum heat transfer is ensured at lower heater length and radius of the heat generating cylinder. Heat transfer rate also increases with the roughness of the cavity.